Motor behaviour of school childhood during recess school - Romero-Ramos, Óscar; Fernández-Rodríguez, Emilio; Merino-Marban, Rafael; González-Campos, Gloria (My University, 2016)
Epidemiological and scientists studies are warning about level of overweight/obesity in our children's schools, and their possible influence on the health of these children along their lives. The combination of physical activity and proper nutrition, appears as one of the basic pillars to keep children in normal weight and healthy state. This study aims to analyze “how much” and “how” children 5 years old use space during school recess. We used the “pedometer” and “behavioral mapping” as registry tools, establishing a motor behaviors in their free play and the possibility of promoting healthy lifestyles, being recess, along with classes of motor skills and physical education, key moments to promote physical activity of our students.
Keywords: Ejercicio físico; Escolares; Niños - Obesidad; Behavioral mapping; Spatial occupation; Obesity; Overweight; Childhood; Physical activity; Health